Challenges for Diagnostic Clarity for Post-stroke Cognitive Impairment and Behavioural Issues in Middle-Income Countries: Case Studies From Malaysia - Yap, Kwong Hsia; Warren, Narelle; Allotey, Pascale; Reidpath, Daniel (Frontiers in Neurology, 2021)
Following stroke, individuals require ongoing screening, diagnosis and monitoring of cognitive impairment. Services and policies around this vary widely between settings, and reports from many countries highlight persistent under-diagnosis of cognitive impairment in the months and years after stroke. Missed and delayed diagnosis of post-stroke cognitive impairment, including dementia, are important factors in shaping the experiences of people so affected and their family members especially in low- and middle-income countries. Drawing upon ethnographic research conducted in Malaysia, this article outlines three case studies to examine the continued health-seeking behaviour after the appearance of salient cognitive and behavioural symptoms that occur after stroke. We highlight the challenges in getting formal diagnostic clarity for cognitive and behavioural symptoms in a rural setting within a middle-income country. No study participants sought help for memory or cognitive problems, partly due to lay awareness of cognitive impairment but more significantly due to health service factors. Despite their elevated risk for dementia, participants were not monitored for cognitive impairment during any follow-up care in various health facilities. Furthermore, caregivers’ attempts to seek help when behavioural issues became untenable were met with multiple barriers in the health system. The journey was complicated by the meanings attached to the reactions towards cognitive symptoms at the community level. We suggest that strategies seek to increase the awareness of post-stroke cognitive and behavioural symptoms, and incorporate clear treatment pathways into the long-term care plans of community-dwelling stroke survivors.